Edge irregular reflexive labeling on sun graph and corona of cycle and null graph with two vertices - Irfan Setiawan; Diari Indriati (Indonesian Journal of Combinatorics, 2021)
Let G(V,E) be a simple and connected graph which set of vertices is V and set of edges is E. Irregular reflexive k-labeling f on G(V,E) is assignment that carries the numbers of integer to elements of graph, such that the positive integer {1,2, 3,...,ke} assignment to edges of graph and the even positive integer {0,2,4,...,2kv} assignment to vertices of graph. Then, we called as edge irregular reflexive k-labelling if every edges has different weight with k = max{ke,2kv}. Besides that, there is definition of reflexive edge strength of G(V,E) denoted as res(G), that is a minimum k that using for labeling f on G(V,E). This paper will discuss about edge irregular reflexive k-labeling for sun graph and corona of cycle and null graph, denoted by Cn ⨀ N2 and make sure about their reflexive edge strengths.